45.7k views
2 votes
Solve for x.
4(2x - 1) - 7 = 4 - x + 6

User Yug Kapoor
by
4.9k points

2 Answers

0 votes

Answer:


x=(21)/(9)

Explanation:

Given : Equation 4(2x - 1) - 7 = 4 - x + 6

We have to solve for x.

Consider the given equation

4(2x - 1) - 7 = 4 - x + 6

Apply distributive rule,
a(b+c)=ab+ac, we have,

8x - 4 -7 = 4 - x + 6

Simplify, by adding similar terms, we have,

8x - 11 = 10 - x

Adding x both side, we ave,

8x + x -11 = 10

Add 11 both side, we have,

9x = 10 + 11

9x = 21

Divide both side by 9, we get,


x=(21)/(9)

User Thomas Leu
by
5.1k points
2 votes
The answer is that x = 21/9.

Start with the original: 4(2x - 1) - 7 = 4 - x + 6
Now distribute the 4: 8x - 4 - 7 = 4 - x + 6.
Now combine the like terms. 8x - 11 = -x + 10.
Now add x to both sides. 9x - 11 = 10.
Now add 11 to both sides. 9x = 21.
And divide by 9 on both side. x = 21/9.
User Mouradif
by
5.4k points